2020
DOI: 10.3390/nano10061231
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Magnetic Nanoparticles in Ferrofluids on Different Templates Investigated by Neutron Reflectometry

Abstract: In this article we review the process by which magnetite nanoparticles self-assemble onto solid surfaces. The focus is on neutron reflectometry studies providing information on the density and magnetization depth profiles of buried interfaces. Specific attention is given to the near-interface "wetting" layer and to examples of magnetite nanoparticles on a hydrophilic silicon crystal, one coated with (3-Aminopropyl)triethoxysilane, and finally, one with a magnetic film with out-of-plane magnetization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 80 publications
0
18
0
Order By: Relevance
“…In contrast, applying the same cleaning procedure to FF25 particles chemically bound to (3-aminopropyl) triethoxysilane (APTES) coated Si wafer (see Fig. S2, ESI †) through amide linkages, results in removal of more than 95% 51,52 of the particles (for details see Fig. S2, ESI †).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, applying the same cleaning procedure to FF25 particles chemically bound to (3-aminopropyl) triethoxysilane (APTES) coated Si wafer (see Fig. S2, ESI †) through amide linkages, results in removal of more than 95% 51,52 of the particles (for details see Fig. S2, ESI †).…”
Section: Discussionmentioning
confidence: 99%
“…Recent polarized neutron reflectivity (PNR) studies showed that wetting and layer formation of NPs in a FF on a Si surface strongly depend on the coating, both of the substrate as well as of the particles, and can be manipulated by magnetic fields. 51,52 In this article, we investigate the selfassembly of nearly monodisperse (size distribution: 5% for the magnetic core and 15% for the shell) magnetic NP, from dilute (0.15 vol%) aqueous solution in the stray field of a magnetic templated substrate, a film of Tb 15 Co 85 with out-of-plane magnetic anisotropy.…”
Section: Introductionmentioning
confidence: 99%
“…Commercially available, monodispersed, single-domain spherical magnetic nanoparticles stabilized in aqueous media (ferrofluids) were used at low solution concentrations (below 1% vol) in the construction of 3D NP assemblies on silicon surfaces [186,187]. Neutron reflectivity studies were performed to investigate the self-assembly process.…”
Section: Magnetic Nanoparticle Assemblies On Surfacesmentioning
confidence: 99%
“…Finally, it should be mentioned that in recent years, the technique of neutron reflectometry (NR) has shown to be very useful to probe magnetic particle configurations on solid surfaces. One can make use of polarized beams also in neutron reflectometry (PNR), and in this way extract both density and magnetization depth profiles near the surface [187]. This is particularly interesting for studying effects of particle coating and applied magnetic field on the self-assembly process of magnetic particles on surfaces with different hydrophobic/hydrophilic character.…”
Section: Figure 15 Topmentioning
confidence: 99%
“…Colloidal magnetic nanoparticles, with well-defined morphology and dimensionality, are of primary importance for both fundamental studies and prospective applications in many technological areas including magnetic storage devices [ 1 , 2 ], ferrofluids [ 3 , 4 , 5 ], magnetic resonance imaging [ 6 , 7 , 8 , 9 , 10 ], drug delivery [ 11 , 12 , 13 , 14 ], bio-separation [ 15 , 16 , 17 ], hyperthermia [ 18 , 19 , 20 , 21 , 22 ], sensing [ 23 , 24 , 25 ], and catalysis [ 26 , 27 , 28 , 29 ]. Amongst them iron-based magnetic materials including iron oxides [ 30 , 31 , 32 ], metallic iron [ 33 , 34 , 35 ], and iron alloys [ 36 , 37 , 38 ] have been extensively studied for many decades.…”
Section: Introductionmentioning
confidence: 99%